Sistem Komputerisasi Pembayaran Administrasi Siswa pada Sekolah Menengah Kejuruan (SMK) Al-Insan Cilegon - Haerani, Reni (LPPM UNIKA Santo Thomas Medan, 2020)
Changes that occur in the field of technology, communication and information are so fast, requiring schools to provide optimal services to their students, especially in Al-Insan Cilegon Vocational School. The student administration payment system at the Al-Insan Cilegon Vocational School still uses the manual method which is written in a financial book. The process can take a long time and the data storage is still in the form of an archive. To overcome these problems computerized systems need to be made. The research method used is descriptive method. Data collection is done by means of observation and interviews. This research uses the Visual Basic programming language. Net and produce a computerized system that can help SMK Al-Insan Cilegon to provide services in the administrative payment of their students. Keywords: computerized system, payment administration, visual basic.net